2015
DOI: 10.3390/f6072281
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of Leaf Water Relations to Climatic and Habitat Water Availability

Abstract: Successful management of forest systems requires a deeper understanding of the role of ecophysiological traits in enabling adaptation to high temperature and water deficit under current and anticipated changes in climate. A key attribute of leaf water relations is the water potential at zero turgor (πtlp), because it defines the operating water potentials over which plants actively control growth and gas exchange. This study examines the drivers of variation in πtlp with respect to species climate of origin an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 38 publications
0
21
2
Order By: Relevance
“…Justification of the use of Ψ tlp as a key functional trait for understanding species distributions along climate or soil water gradients in ecological studies has relied on its relationship with leaf water potential at stomatal closure, that is, stomatal sensitivity (Bartlett et al ; Maréchaux et al ; Meinzer et al ; Mitchell and O'Grady ). However, as previously discussed, this relationship has only been demonstrated with very few species (Brodribb et al ; Mitchell et al ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Justification of the use of Ψ tlp as a key functional trait for understanding species distributions along climate or soil water gradients in ecological studies has relied on its relationship with leaf water potential at stomatal closure, that is, stomatal sensitivity (Bartlett et al ; Maréchaux et al ; Meinzer et al ; Mitchell and O'Grady ). However, as previously discussed, this relationship has only been demonstrated with very few species (Brodribb et al ; Mitchell et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Drought-related mortality and die-back are increasingly being reported from vegetation communities globally (Allen et al 2010). Consequently, there is growing interest in being able to predict plant species vulnerability to water limitations from physiological traits such as leaf turgor loss point, to understand potential changes in plant distributions and ecosystem structure (Bartlett et al 2014;Maréchaux et al 2015;Mitchell and O'Grady 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we observed no relationships between climate of origin and either drought tolerance or water use. For example, Mitchell and O'Grady (2015) compiled a database for 174 woody species across a range of temperature and precipitation in Australia and showed that natural habitat water availability (precipitation and temperature) was significantly related to plant drought tolerance, with species from drier and hotter regions having more negative turgor loss points than species from cooler and wetter regions. This is in contrast to previous studies, which have suggested that drought tolerance measures such as turgor loss point, can predict species distribution and mortality (Engelbrecht et al 2007, Bartlett et al 2012.…”
Section: Relationships Between Morphological Traits Water Use and Dmentioning
confidence: 99%
“…These responses can vary among plant taxa depending on how they have evolved to deal with drought; taxa that are adapted to frequent droughts may have responses that optimize their survival during drought and recovery and growth afterwards. We focus here on the osmotic potential at turgor loss point (π TLP ), or the wilting point, an ecophysiological trait commonly used to characterize plant drought tolerance (Bartlett, Scoffoni, Ardy, et al, ; Lenz, Wright, & Westoby, ; Mitchell & O'Grady, ). We also measured leaf water potential (Ψ leaf ) to characterize the level of osmotic stress the plants were experiencing, with a lower (more negative) value indicating higher solute concentration and less water in the leaves (Lenz et al, ).…”
Section: Introductionmentioning
confidence: 99%